ESG integration and investor confidence: A comparative study of islamic and conventional banks in OIC countries - Abdani, Fadlil; Nisa’yanayiroh, Izzun; Rudianto, Nur Ahmad Ricky (Journal of Multiperspectives on Accounting Literature, 2026)
Purpose: To investigate the impact of the Islamic and conventional banks on the financial performance (ROA) of some OIC countries through ESG disclosures. Methodology/approach: This research uses a quantitative methodology based on panel data from annual and sustainability reports for banks in OIC member states, covering the years 2020–2023. Findings: Due to higher compliance costs, ESG disclosure negatively affects ROA in Islamic banks, whereas large banks overcome this through economies of scale. On the other hand, ESG improves ROA in conventional banks, but this advantage decreases with larger bank size. Practical implications: Islamic banks might leverage their scale to manage ESG expenditures, while conventional banks are better off pursuing the best ESG strategy until the point of diminishing returns. OIC regulators should design ESG frameworks to be compatible with the operational models of both banking systems. Originality/value: This study examines the approach it takes to compare the methods by which ESG values are transmitted through two different banking systems in the OIC region. It highlights that bank asset size moderates these relationships in opposite directions for Islamic versus conventional banks.